Pengaruh Pemberdayaan Keluarga terhadap Keputusan Pemeriksaan Antenatal Care Lengkap pada Ibu Hamil - Sujawaty, Sri; Olii, Nancy; Rasyid, Puspita Sukmawaty; Yulianingsih, Endah; Podungge , Yusni (Jurnal Locus Penelitian dan Pengabdian, 2025)
Increasing the empowerment of pregnant women strengthens their capacity to access and control decisions, resources, and antenatal care (ANC) support services. ANC is an essential periodic monitoring to detect and manage the risk of pregnancy early. This study aims to evaluate the extent to which the empowerment of pregnant women affects the implementation of ANC examinations. The research uses an analytical method with a cross-sectional approach. Pregnant women's empowerment is an independent variable, while compliance with ANC is a bound variable. A total of 32 pregnant women who came to the East City Health Center of Gorontalo were made respondents through accidental sampling techniques. Data on the level of empowerment was collected through filling out questionnaires, while data on compliance with ANC was obtained from medical records. Data analysis was carried out using the chi-square test. The results showed that 66.7% of mothers with low levels of empowerment did not undergo ANC according to the provisions, while 88.2% of mothers with high empowerment underwent ANC according to standards. The results of the statistical test showed a value of p = 0.028, which means that there is a significant relationship between the empowerment of pregnant women and compliance with ANC examinations. Pregnant women who have a good level of empowerment tend to be able to make the right decisions in accessing pregnancy services, so they can undergo ANC at least four times during pregnancy: once in the first trimester, once in the second trimester, and twice in the third trimester. It is recommended that health workers play an active role in increasing the empowerment of pregnant women through counseling activities that also involve family members, especially husbands, in order to create stronger support in the pregnancy process.